2019
DOI: 10.3390/met9101044
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Copper Thermocompression Diffusion Bonding under Vacuum: Microstructural and Mechanical Characteristics

Abstract: The optimization of the autogenous diffusion copper bonding via thermocompression at vacuum environment was investigated. The influence of various bonding parameters on the interdiffusion efficiency was studied in detail at the micro (SEM-EBSD) and nano (TEM) scales. Bonding at 1000 °C for 90 min under pressure (10 MPa) presented optimum structural and mechanical results. Under these conditions, interdiffusion phenomena were observed at a significant extent through the swelling transformation of existing fine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Denote it by β E , then the expression (6) can be written as E(x) = E av β E . The term in parentheses of expression (6) is always less than one and on the surface of the protrusion at x = h vanishes. Therefore, the main is the second term, the value of which is maximum at minimum x, i.e., at x = h and at the x = d c simultaneously.…”
Section: The Analytical Equation Of a Glow Discharge Energy Stability While Treatment And Welding Of Metals Depending On Cathode Surface mentioning
confidence: 99%
See 1 more Smart Citation
“…Denote it by β E , then the expression (6) can be written as E(x) = E av β E . The term in parentheses of expression (6) is always less than one and on the surface of the protrusion at x = h vanishes. Therefore, the main is the second term, the value of which is maximum at minimum x, i.e., at x = h and at the x = d c simultaneously.…”
Section: The Analytical Equation Of a Glow Discharge Energy Stability While Treatment And Welding Of Metals Depending On Cathode Surface mentioning
confidence: 99%
“…Known works consider the possibility of application of gas discharges technique in the field of thin films deposition, metals surfacing, treatment and modification of metals before welding [2][3][4][5]. Still, as practice has shown, diffusion welding [6] and thermal and chemical-thermal surface treatment [7] are the most appropriate. This is due to the high technological capabilities of the glow discharge, which in these processes can serve both a processing tool and a source of thermal energy for their implementation simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the quality of a diffusion bond is sensitive to various bonding parameters such as temperature, pressure, and duration, as also indicated in the American Society of Mechanical Engineers (ASME) Boiler and Pressure Vessel Code, Section IX under Part QW. In addition, selecting optimum diffusion bonding conditions would differ for varying alloys, and would involve consideration of each alloys' mechanical properties, microstructures, and chemical composition [18,19]. For example, Gietzelt et al conducted diffusion bonding on austenitic, ferritic, and martensitic stainless steels and reported that the highly alloyed steels required more severe conditions for a sound diffusion bond to be achieved [20].…”
Section: Introductionmentioning
confidence: 99%